2023
DOI: 10.3390/pharmaceutics15092358
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Responsive Hydrogels Encapsulating Targeted Core–Shell Nanoparticles as Injectable Drug Delivery Systems

Elif Gulin Ertugral-Samgar,
Ali Murad Ozmen,
Ozgul Gok

Abstract: As therapeutic agents that allow for minimally invasive administration, injectable biomaterials stand out as effective tools with tunable properties. Furthermore, hydrogels with responsive features present potential platforms for delivering therapeutics to desired sites in the body. Herein, temperature-responsive hydrogel scaffolds with embedded targeted nanoparticles were utilized to achieve controlled drug delivery via local drug administration. Poly(N-isopropylacrylamide) (pNIPAM) hydrogels, prepared with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The incorporation of organic or inorganic particles into polymeric scaffolds like hydrogels has been proven to better control the pharmacokinetic profiles of drug-loaded molecules as well as to improve their stability and increase local drug concentration, providing a drug reservoir at the site of administration [43][44][45][46][47][48][49]. Moreover, it has been reported that hydrogel/nanoparticle complex systems display improved rheological and mechanical properties, which in turn enhance their printability and injectability [38,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of organic or inorganic particles into polymeric scaffolds like hydrogels has been proven to better control the pharmacokinetic profiles of drug-loaded molecules as well as to improve their stability and increase local drug concentration, providing a drug reservoir at the site of administration [43][44][45][46][47][48][49]. Moreover, it has been reported that hydrogel/nanoparticle complex systems display improved rheological and mechanical properties, which in turn enhance their printability and injectability [38,50,51].…”
Section: Introductionmentioning
confidence: 99%